Acute Axonal Polyneuropathy Following Honey-Bee Sting: A Case Report. (May 2014) - Saini, Arushi Gahlot; Sankhyan, Naveen; Suthar, Renu; Singhi, Pratibha
Hymenoptera stings lead to a myriad of neurologic manifestations by the mechanism of immediate or delayed hypersensitivity reactions. The more common form of polyneuropathy associated with these stings is the acute inflammatory demyelinating type. We describe a 6-year-old girl, who developed progressive, symmetrical, ascending weakness within 3 days after a bee sting. Serial nerve conduction studies confirmed acute, motor-predominant axonal polyneuropathy. Use of intravenous immunoglobulin induced halt of progression, prompt stabilization and a gradual recovery. This case highlights that even a single honey-bee sting can result in acute-onset axonal variety of polyneuropathy in children.